CLASSROOM MANAGEMENT STRATEGIES FOR ENGLISH TEACHERS - Karimova Asalbonu Doniyor qizi (TADQIQOTLAR, 2025)
Annotation: This article explores effective classroom management strategies specifically designed for English language teachers. It emphasizes the creation of a positive and productive learning environment that supports language acquisition and student engagement. The article offers practical techniques and examples for maintaining order, fostering participation, and addressing common challenges in English classrooms.